In situ mitochondrial biomineralization for drug-free cancer therapy - Ma, Zhaoyu (2024)
The common clinical chemotherapy often brings serious side effects to patients, mainly due to the off-target and leakage of toxic drugs. However, this is fatal for some specific clinical tumors, such as brain tumors and neuroma. This study performs a drug-free approach by encapsulating black phosphorus (BP) and calcium peroxide (CaO2) in liposomes with surface-modified triphenylphosphonium (BCLT) to develop mitochondria targeting calcification for cancer therapy without damaging normal cells. BCLT preferentially accumulates inside tumor mitochondria and then is activated by near-infrared (NIR) laser irradiation to produce abundant PO4 3- and Ca2+ to accelerate in situ mitochondrial mineralization, leading to mitochondrial dysfunction and cancer cell death. More importantly, both PO4 3- and Ca2+ are essential components of metabolism in the body, and random gradient diffusion or premature leakage does not cause damage to adjacent normal cells. This achievement promises to be an alternative to conventional chemotherapy in clinical practice for many specific tumor types.